The exploration of continuous learning intention in STEAM education through attitude, motivation, and cognitive load - Chih-Hung Wu; Chih-Hsing Liu; Yueh-Min Huang (SpringerOpen, 2022)
Highlights The STEAM learning cycle was proposed to describe four phases for successful STEAM learning. Affect factors of learning intention in STEAM education were investigated. Motivation factors positively influences perceived usability and learning attitude. Cognitive load has a significant negative effects influences perceived usability. Perceived usability directly influences learning intention and strengthens the relationship between attitudes and intention.